Aspectos da ilocução na interacção verbal em contexto pedagógico - Carla Alves Aires (Universidade do Minho, 2002)
This text adopts basically discourse analysis procedures, as a linguistic analysis of discursive occurrences in real contexts (Stubbs, 1983). We selected as our object vebal interactions produced in the classroom, giving special attention to teacher talk, being our aim to gather information about how do teachers talk and how they show or mitigate their power towards pupils. We followed some investigations made by Bernstein (1981) about how power relations are reproduced and we tried to connect them with speech acts theory (Searle, 1976) and the verbal politeness theory (Brown and Levinson, 1987). We analysed a corpus constituted by three lessons (2nd cycle), of Language Arts (Portuguese) that we described through categories conceived for the analysis of the illocutionary speech acts. The analysis allowed to verify that there is a strong directivity and imposition in techers talk, visible not only in the high frequency of directive acts, but also in the low frequency comissive and expressive acts.